PROMOTING PRODUCT SERVICE SYSTEM FOR MOTORCYCLE: A STUDY OF RIDESHARING PROGRAM INTENTION FOR UNIVERSITY STUDENTS - Wiyono, Azis Slamet; Astuti, Septin Puji (Jurnal Ilmiah Teknik Industri, 2019)
The need to reduce air pollutions produced by motor vehicle and traffic congestion is prominent as it improves human health and environmental destruction mitigation. Ridesharing programme is an effort to reduce traffic congestion without preventing people doing mobility and prohibiting them to buy motor vehicle. This paper addresses to investigate the determinant of university student to ridesharing programme. Four variables with descrete items were provided t respondents to be self selected. Those are home address status, type of driving licence, student?s travel behavior to university and intention of student to ridesharing programme. Those variables are analysed in to three models. By using Logistic Regression statictical analysis, this study shows that ridesharing programme intention is influenced by the behavior of student to travel to university. Meanwhile, student travel behavior is influenced by home address status and the ownership of driving licence of students.